Characterization of optical mechanical switch (OMS) - Wong, Yin Leng (2004)
This new generation network nowadays needs to fulfill the demands of the new information age, which requires improved scalability, flexibility, and dynamic delivery of communication services. An evolution of the network is underway to meet this demand. The evolution introduces new network elements supporting an architecture that is better suited for the dynamic global distribution of broadband based services. As such, the next major step in the progression is the wide scale deployment of intelligent optical switches. The purpose of this study was to investigate the characteristics and behavior of an optical mechanical switch (OMS) in order to implement efficiently into optical communication system. Extensive simulations based on Mathlab were performed and measurement based on physical connection is set up. Evaluation was based on various expressions like crosstalk, isolation, insertion loss and control signals to OMS. Practical channel separation of spacing and bandwidth needs to be determined to meet crosstalk and other parameters. The measurement is carried out by implying 2 x 2 Newport Optical Switch, TLS and OSA. Two input wavelengths of 1550.12 nm (Channel 1) and 1549.32 nm (Channel 2) are used to carry out the measurement in the system. Results are made from comparison between the simulation and measurement data. These results showed significant improvement in overall performance especially in Channel 1. The framework used for this measurement is general enough for further investigation by either evaluating other parameters of the switch or by extending its application in the optical communication network